Carbon-rich cyclopentadienyl ruthenium allenylidene complexes. (13th May 2016) - Spörler, Susanne; Strinitz, Frank; Rodehutskors, Philipp; Müller, Lisa; Waterloo, Andreas R.; Dürr, Maximilian; Hübner, Eike; Ivanović-Burmazović, Ivana; Tykwinski, Rik R.; Burzlaff, Nicolai
Abstract : Ruthenium allenylidene complexes based on carbon-rich polyaromatic moieties have been synthesized with interesting intermolecular π-interactions. Abstract : Ruthenium allenylidene complexes with carbon-rich polyaromatic moieties have been synthesized by using [RuCl(η 5 -C5 H5 )(PPh3 )2 ] (η 5 -C5 H5 = cyclopentadienyl) as a precursor and the propargyl alcohols 10-ethynyl-10-hydroxyanthracen-9-one (ACO), 13-ethynyl-13-hydroxypentacen-6-one (PCO), 1-phenyl-1-(pyren-1-yl)prop-2-yn-1-ol (PyrPh), 9-ethynyl-9 H -fluoren-9-ol (FN) and 6-ethynyl-6 H -benzo[ cd ]pyren-6-ol (BPyr) as ligands. The resulting cationic allenylidene complexes, [Ru(η 5 -C5 H5 )(CC(AO))(PPh3 )2 ]PF6 (1 ), [Ru(η 5 -C5 H5 )(CC(PCO))(PPh3 )2 ]PF6 (2 ), [Ru(η 5 -C5 H5 )(CC(PyrPh))(PPh3 )2 ]PF6 (3 ), [Ru(η 5 -C5 H5 )(CC(FN))(PPh3 )2 ]PF6 (4 ), and [Ru(η 5 -C5 H5 )(CC(BPyr))(PPh3 )2 ]PF6 (5 ) show interesting intermolecular π-interactions in the solid-state structure as well as solution state complexation with pyrene (documented by Job's plots experiments). CV data indicate possible Ru(ii )/Ru(iii ) oxidation, as well as the potential reduction of the carbon-rich allenylidene moiety.